BS EN 50288-13-1. Multi-element metallic cables used in analogue and digital communication and control. Part 13-1. Sectional specification for outer screened cables characterised up to 2000 MHz. Horizontal and building backbone cables (18th May 2020) - British Standards Institution,
No abstract available